2022
DOI: 10.3390/pharmaceutics14030627
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetic Assessment of Oral Proglumide in Those with Hepatic Impairment

Abstract: Proglumide is an orally administered cholecystokinin receptor antagonist that was found to improve nonalcoholic steatohepatitis, reverse liver fibrosis, and decrease incidence of hepatocellular carcinoma (HCC) in animal models. The current investigation aimed to test the pharmacokinetics and safety of proglumide in subjects with hepatic impairment compared with healthy controls. In this translational study, subjects with confirmed cirrhosis, Child-Pugh stage A or B, or healthy controls were recruited for a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, this difference could be due to the fact that more of the Cohort 3 participants had afternoon appointments and their proglumide blood levels had started to decline. We previously showed 28 in participants with cirrhosis and healthy controls, peak blood levels occurred within 1 hour after injections. Once maximum, the drug concentration was reduced to half in about 2.5 hours (C max1/2 ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, this difference could be due to the fact that more of the Cohort 3 participants had afternoon appointments and their proglumide blood levels had started to decline. We previously showed 28 in participants with cirrhosis and healthy controls, peak blood levels occurred within 1 hour after injections. Once maximum, the drug concentration was reduced to half in about 2.5 hours (C max1/2 ).…”
Section: Resultsmentioning
confidence: 93%
“…35 We recently completed a pharmacokinetic single‐dose study testing proglumide in participants with Child‐Pugh A and B cirrhosis and found the C max and time to reach maximum plasma concentration (T max ) were comparable to that of healthy controls. 28 Since the current study was the first clinical trial in participants with NASH, we selected a proglumide dose that was lower and a dose higher than the 1,200 mg/day dosing used in earlier peptic ulcer disease studies. Although all three doses were well tolerated in participants with NASH, we observed the greatest decline in ALT and liver stiffness by FibroScan using the highest dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the recommendation was to use the 1200 mg per day dose for the current study. Pharmacokinetic studies were also performed with proglumide in healthy controls and in patients with hepatic impairment, which revealed rapid oral absorption and renal excretion [15]. In animal models of chronic pancreatitis, we found that proglumide decreased pancreatic fibrosis and inflammation [16].…”
Section: Introductionmentioning
confidence: 82%
“…Proglumide was dispensed from the investigational pharmacy at baseline and at the week 4 and week 8 visits and prescribed as one capsule by mouth three times daily for a total daily dose of 1200 mg. The dose and dosing schedule were based upon the results of a prior study involving subjects with metabolic-associated hepatic steatosis [14] and a pharmacokinetic study involving healthy controls and subjects with hepatic impairment [15]. The protocol allowed for the dose to be reduced from 1200 mg/day to 800 mg/day for drug-related side effects.…”
Section: Interventionmentioning
confidence: 99%